GPs' opinions of public and industrial information regarding drugs: a cross-sectional study - Gunnarsson Ronny; Mehlig Kirsten; Björkelund Cecilia; Skoglund Ingmarie; Möller Margareta (BMC, 2011)
Abstract Background General Practitioners GP in Sweden prescribe more than 50% of all prescriptions. Scientific knowledge on the opinions of GPs regarding drug information has been sparse. Such knowledge could be valuable when designing evidence-based drug information to GPs. GPs' opinions on public- and industry-provided drug information are presented in this article. Methods A cross-sectional study using a questionnaire was answered by 368 GPs at 97 primary-health care centres PHCC. The centres were invited to participate by eight out of 29 drug and therapeutic committees DTCs. A multilevel model was used to analyse associations between opinions of GPs regarding drug information and whether the GPs worked in public sector or in a private enterprise, their age, sex, and work experience. PHCC and geographical area were included as random effects. Results About 85% of the GPs perceived they received too much information from the industry, that the quality of public information was high and useful, and that the main task of public authorities was to increase the GPs' knowledge of drugs. Female GPs valued information from public authorities to a much greater extent than male GPs. Out of the GPs, 93% considered the main task of the industry was to promote sales. Differences between the GPs' opinions between PHCCs were generally more visible than differences between areas. Conclusions Some kind of incentives could be considered for PHCCs that actively reduce drug promotion from the industry. That female GPs valued information from public authorities to a much greater extent than male GPs should be taken into consideration when designing evidence-based drug information from public authorities to make implementation easier.